Health-related quality of life in patients with functional dyspepsia - Bjelović, Miloš; Zarić, Nemanja; Babič, Tamara; Dragičević, Igor; Ćorac, Aleksandar; Trajković, Goran (Vojnosanitetski pregled, 2017)
Background/Aim. Recent population based studies have proved that patients with functional dyspepsia (FD) have a significantly impaired health-related quality of life HRQoL as compared to general population. The aim of the study was to evaluate the impact of FD on (HRQoL) in patients treated in primary healthcare settings in Serbia. Methods. The study involved 1,448 patients with FD. The diagnosis was made by a general practice physician or gastroenterologist using the Rome III diagnostic criteria. The Serbian version of the questionnaire for the assessment of HRQoL of the U.S. Department of Health and Human Services’ Centers for Disease Control and Prevention (HRQoL-4 item CDC) was used for data collection, while descriptive statistical measurements were applied to calculate standard deviation, frequency as well as multiple logistic regression model. Results. Out of the total number of patients, 41.8% assessed their health condition as seriously disordered or poor. The mean values of health disorder duration over the last 30 days was 11.8 days, disordered physical health 7.2 days, mental disorder 6.3 days, and activity limitation 5.1 days. Also, 29.7%, 15.2%, 12.8% and 10.7% of the patients reported ≥ 14 unhealthy days, ≥ 14 physically unhealthy days, ≥ 14 mentally unhealthy days and ≥ 14 activity limitation days, respectively. Conclusion. From patients’ perspective, FD has a significant impact on HRQoL. In this study, 41.8% of the patients described their health status as fair or poor, and FD significantly affects all aspects of life, both mental and physical. The recognition of that impact is probably the most important step towards appropriate treatment and decreasing HRQoL impairment in patients with FD.
Keywords: dyspepsia; quality of life; depression; anxiety; surveys and questionnaires